1985
DOI: 10.1029/ja090ia07p06275
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind flow about the outer planets: Gas dynamic modeling of the Jupiter and Saturn bow shocks

Abstract: Pioneer 10 and 11 and Voyager 1 and 2 observations are used to study global aspects of the solar wind interaction with Jupiter and Saturn. Solar wind measurements before and after the encounters are used to determine average upstream flow parameters at 5 and 9 AU. Bow shock and magnetopause position are found to vary as the fourth root of dynamic pressure at Jupiter and the sixth root at Saturn. The average distances to the nose of the magnetopause based upon the Pioneer and Voyager boundary crossings for Jupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
207
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(230 citation statements)
references
References 61 publications
21
207
1
1
Order By: Relevance
“…The detectors on the Cassini mission are speci®cally designed to detect and`image' such energetic neutral atoms emanating from planetary magnetospheres. The magnetosphere imaging instrument (MIMI) 8 uses an ion and neutral camera (INCA) sensor that rejects charged particles and can detect energetic neutral atoms over the velocity range ,10 3 to ,10 4 km s -1 using a time-of-¯ight technique, with crude separation into light (that is, H, He) and heavy (that is, O, S) components. A second MIMI sensor, the charge±energy±mass spectrometer (CHEMS) is capable of determining independently the charge state, mass, and energy of ions over the range of ,3 to ,220 keV per charge.…”
Section: Ion Acoustic Wavesmentioning
confidence: 99%
“…The detectors on the Cassini mission are speci®cally designed to detect and`image' such energetic neutral atoms emanating from planetary magnetospheres. The magnetosphere imaging instrument (MIMI) 8 uses an ion and neutral camera (INCA) sensor that rejects charged particles and can detect energetic neutral atoms over the velocity range ,10 3 to ,10 4 km s -1 using a time-of-¯ight technique, with crude separation into light (that is, H, He) and heavy (that is, O, S) components. A second MIMI sensor, the charge±energy±mass spectrometer (CHEMS) is capable of determining independently the charge state, mass, and energy of ions over the range of ,3 to ,220 keV per charge.…”
Section: Ion Acoustic Wavesmentioning
confidence: 99%
“…The factor of 1.16 has been introduced to account for the 4% abundance of He 2+ in the solar wind which has a temperature approximately 4 times greater than the protons, as found by Slavin et al [1985]. Kanani et al [2010] explored the sensitivity of the model to the value of this factor, as well as the solar wind speed and the solar wind temperature but found that it was insensitive to varying these parameters within reasonable limits.…”
Section: 1002/2014ja019774mentioning
confidence: 99%
“…In addition, the two boundaries may respond differently to the solar wind dynamic pressure [Slavin et al, 1985;Hendricks et al, 2005] hence a change in the dynamic pressure is not necessarily proportional to the magnetosheath subsolar and polar thicknesses i.e. the planetocentric distances between the magnetopause and the bow shock at X KSM = 0 and Z KSM = 0 respectively (neglecting aberration).…”
Section: Magnetic Field In Saturn's Magnetosheathmentioning
confidence: 99%
“…At 10 AU (1 AU = 1.5 × 10 8 km), typical values for k B T e and n e are ~1 eV [Slavin et al, 1985] and ~0.05 cm -3 [Crary et al, 2005] respectively yielding λ D ~ 30 m.…”
Section: Definition and Characteristics Of Plasmasmentioning
confidence: 99%
See 1 more Smart Citation